Screening of occupational lung disease in Malaysia - Samsuddin, Niza (2008)
Screening of occupational lung disease in Malaysia is part of health surveillance activities which are regulated under Occupational Safety and Health Act 1994. Health surveillance means biological and health effects monitoring due to occupational chemical exposure at work that implicates pre-employment examination, medical removal protection, pre-placement medical examination, disability assessment, workplace inspection, diagnoses of occupational lung disease, notification and referral to physician. Health surveillance has therefore both prevention and clinical focuses whereas screening of occupational lung diseases is a clinical focus. In Malaysia Occupational Health Doctor (OHD) and physician in the hospital both conduct screening of occupational lung diseases. The needs of health surveillance and screening of occupational lung disease among workers by OHD are dependent on employer request, chemical health risk assessment and industrial hygiene report. The system available enables Department of Safety and Health Malaysia (DOSH) to supervise and enforce on the control of chemical exposure and improve in the working environment that prevents further jeopardizing worker's health. It also provides referral cases to physician to the hospitals. Screening and diagnoses of occupational lung diseases in clinical setting has little implications on the medical treatment in most of the lung disease patients. In Malaysia, occupational lung diseases and other occupational diseases are under reported for many reasons. Problems in diagnoses in terms of determining exposure assessment, screening tools and cost are among other reasons being discussed. Integration of public health approaches into the clinical setting and team approach will contribute to improvement in diagnosis, treatment and prevention of occupational lung disease.